e-Aduan: A solution to improve the quality of services in UiTM Pahang on management perspective / Razulaimi Razali, Khairul Nizam Abd Halim and Mohd Izuan Ibrahim - Razali, Razulaimi; Abd Halim, Khairul Nizam; Ibrahim, Mohd Izuan (2008)
Feedback from customers is an effective method to identify the quality of services and facilities provided by a university. The effectiveness of making respond to customers' feedback also depends on an effective workflow. By having an effective method and workflow, the action from the management to improve the quality of services and facilities can be done immediately and effectively. To fulfill this purpose the researchers have developed an online system called e-Aduan. e-Aduan is a platform for the customers to complaint and comment on the services and facilities provided by university. Through e-Aduan the complaints can be retrieved immediately by the management. Through this platform the researchers have also identified workflow procedures to be followed by the management to address customers' complaints and comments. Customers also have an opportunity to view the status of each of their complaints and comments. This new scenario produces good impact to both customers and management; customers now have a platform to communicate their dissatisfaction and the management will be able to act immediately upon any customers' feedback. Researchers believe e-Aduan and the effective workflow can be applied to other sector nationally and internationally. The strength of this research is on the combination of the effective method (e-Aduan) and effective workflow.